The Effect of Current Ratio and Debt to Equity Ratio on Return on Equity at PT. Telkom Indonesia Tbk Period 2016-2023 - Faisal Pratama; A Idun Suwarna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to evaluate the impact of three variables: Current Ratio, Debt to Equity Ratio, and Return on Equity. This study uses an associative quantitative approach. The financial statements of PT. Telkom Indonesia Tbk from 2016 to 2023 are the subjects of this study, and the method used to collect data is documents. Descriptive analysis, correlation analysis, determination coefficient analysis, multiple linear regression analysis, and hypothesis testing (t-test and F-test) are used to analyze the data. The results show that Return on Equity is influenced by Current Ratio and Debt to Equity Ratio. PT Telkom, and Current Ratio partially affects Firm Value. Tempo from 2016 to 2023 for Indonesia Tbk